PERBEDAAN PERKEMBANGAN MOTORIK PADA ANAK AUTIS ANTARA YANG MENDAPAT TERAPI DIET CFGF DENGAN DIET PROVOKASI ELIMINASI DI KOTA SEMARANG - Mohammad Jaelani; Joko Priyatno (Poltekkes Kemenkes Semarang, 2017)
Background : There are at least two dietary recommendations for people with autism, a strict diet of CFGF that eliminates dietary sources of casein and gluten in the diet and a diet of elimination provocation that still tolerates foods containing Casein or gluten which after the provocation of elimination tests does not cause allergies in the individual.Objective : This study was conducted to determine differences in motor development in children with autism between who received CFGF diet therapy with a diet of provocation of elimination in the city of Semarang.Method : To achieve the expected research objectives, descriptive research will be conducted using comparative study method that is comparing the energy intake, protein intake and autistic children's development body between those who run the CFGF diet and provocation of elimination using Longitudinal research design that measures the variables for three months ahead.Results : The results of the analysis in Table 22 showed that there was a difference between the CFGF Diet Group and the Elimination Provocation Diet on the variable energy intake level, protein intake level and nutritional status (pvalue 0.05). While in the variable of motor development statistically there is no difference (pvalue 0,05).Conclusion : There is a difference in the level of adequacy of energy, protein and nutritional status between children who run the CFGF Diet with children who are on diet therapy Provocation of elimination. And there is no difference in motor behavior between children who run the CFGF Diet with children who are on diet therapy Provocation of elimination.